Efficient CRISPR/Cas9‐Based Genome Engineering in Human Pluripotent Stem Cells. (1st January 2016) - Kime, Cody; Mandegar, Mohammad A.; Srivastava, Deepak; Yamanaka, Shinya; Conklin, Bruce R.; Rand, Tim A.
Abstract: Human pluripotent stem cells (hPS cells) are rapidly emerging as a powerful tool for biomedical discovery. The advent of human induced pluripotent stem cells (hiPS cells) with human embryonic stem (hES)–cell‐like properties has led to hPS cells with disease‐specific genetic backgrounds for in vitro disease modeling and drug discovery as well as mechanistic and developmental studies. To fully realize this potential, it will be necessary to modify the genome of hPS cells with precision and flexibility. Pioneering experiments utilizing site‐specific double‐strand break (DSB)–mediated genome engineering tools, including zinc finger nucleases (ZFNs) and transcription activator–like effector nucleases (TALENs), have paved the way to genome engineering in previously recalcitrant systems such as hPS cells. However, these methods are technically cumbersome and require significant expertise, which has limited adoption. A major recent advance involving the clustered regularly interspaced short palindromic repeats (CRISPR) endonuclease has dramatically simplified the effort required for genome engineering and will likely be adopted widely as the most rapid and flexible system for genome editing in hPS cells. In this unit, we describe commonly practiced methods for CRISPR endonuclease genomic editing of hPS cells into cell lines containing genomes altered by insertion/deletion (indel) mutagenesis or insertion of recombinant genomic DNA. © 2016 by John Wiley & Sons, Inc.